First-Principles Study of Electronic and Magnetic Properties and Tetragonal Distortion of the Heusler Alloy $Mn_2NiAl$ (Journal of Atomic and Molecular Sciences, 2011)
The crystal structure, tetragonal distortion, magnetism, electronic structure and pressure response of $Mn_2NiAl$ are calculated by first-principles method based on the density functional theory. The calculations show, the equilibrium structure of $Mn_2NiAl$ in the cubic austenitic phase is the MnMnNiAl structure with Mn atoms occupy $A$ and $B$ sites and two Mn atoms occupy inequivalent positions. In the process of transform \u00a0from a cubic to a tetragonal structure, $Mn_2NiAl$ alloys exhibit a stable martensitic phase near $c/a = 1.24.$ In both the austenite and martensite phases, Mn atoms are the main contributors to the magnetism in $Mn_2NiAl,$ $Mn_2NiAl$ alloys show ferrimagnetism due to antiparallel but unbalanced magnetic moments of Mn(A) atom and Mn(B) atom. The direct $d-d$ exchange interactions between Mn(A) atom and Mn(B) atom are weak because of small overlap of $d$-projected DOS of Mn(A) atom and Mn(B) atom nearby the Fermi level, but the intra-atomic interactions in Mn atoms are strong, this is the reason why the $Mn_2NiAl$ alloys show ferrimagnetism. The findings strongly suggests that $Mn_2NiAl$ alloys would behave like a magnetic shape memory alloy.
Keywords: first-principles; tetragonal distortion; martensite phase transformation; ferrimagnetism.